Analysis of mesiodistal angulations of preadjusted brackets - Marcos Rogério de MENDONÇA; Ana Caroline Gonçales VERRI; Aubrey Fernando FABRE; Osmar Aparecido CUOGHI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Manufacturers offer various prescriptions of preadjusted brackets for use in the "straight-wire" orthodontic technique. However, the need to incorporate bends in the rectangular wires during orthodontic finishing has led to concerns regarding the type of prescription chosen and the credibility of information provided by the manufacturer. The aim of this study was to compare the slot angulations of Roth prescription preadjusted metallic brackets for the maxillary left central incisor and maxillary left canine. For each tooth type, 10 brackets of three commercial brands (GAC, Forestadent and Morelli) were selected. Two individual metal matrices for brackets and tooth positioning were made for each group of teeth. Captured images were obtained by standardized ortho-radial photography with a digital camera. Images were exported and analyzed with the Image J software package. One-way ANOVA and Tukey statistical analyses were performed at the 5% significance level. For brackets of the maxillary left central incisor, differences in mean angulation were observed between the Morelli and GAC groups (p < 0.01) and between the Forestadent and GAC groups (p < 0.01). For brackets of the maxillary left canine, differences in mean angulation were found between the Morelli and GAC groups (p < 0.01) and between the Morelli and Forestadent groups (p < 0.05). In conclusion, despite their same prescription name, the different brands exhibited significantly different angulation measurements.